Costs and return to scale analysis of extending the offer of pre-exposure prophylaxis (PrEP) to key populations aged 15–17 years old in two Brazilian cities - Andreia Costa Santos; Joilson Nascimento Paim; Patricia Coelho de Soarez; Natacha Cerchiari; Laio Magno; Ines Dourado; Alexandre Grangeiro (PLoS ONE, 2025)
In Brazil, HIV infection incidence is increasing, particularly among men who have sex with men (MSM) and transgender women (TGW). Pre-exposure prophylaxis (PrEP) is an effective prevention strategy, offered for free for those 15 years and over, in the Brazilian National Health System (SUS), but without a consistent demand creation strategy (DCS) to support the Sustainable Development Goals targets. The objectives of this study are to assess (1) the total incremental cost, and average total incremental costs of PrEP delivery, including DCS, targeting MSM and TGW adolescent aged 15–17 years old, and (2) the potential gains of scale for the expansion of PrEP at SUS, based on different scenarios to reach the UNAIDS goals for HIV targets. We estimated the total incremental and average total incremental cost, and the gains of scale for the expansion of PrEP delivery in SUS using Cobb-Douglas functions. The average total incremental cost per PrEP delivery was estimated at USD 321 in Salvador and USD 254 in São Paulo. Gains of scale were observed in both study settings and nationally for the Brazilian SUS. Our estimates show that investments in expanding PrEP delivery to 15–17 years old will likely reduce average total incremental costs to the Brazilian SUS. However, a cost-effectiveness analysis would be required to assess whether investments in an expansion of PrEP delivery would maximise the benefits of reducing the incidence of HIV/AIDS among the target population compared to the current Brazilian SUS practices.